Improvement of the Mechanism for Increasing the Efficiency of Taxes in Increasing the Local Budget Opportunities - Shakhriyor Parmanov; Parviz Usmonov (International Journal on Economics, Finance and Sustainable Development, 2022)
Based on the analysis of the current state of local budgets in Uzbekistan, the article contains opinions on increasing the effectiveness of taxes attached to them in increasing their financial capabilities, and based on the analysis, suggestions and recommendations are formulated. An analysis of the opinions of economists on improving the efficiency of local taxes is provided.